The Effect of Green Intellectual Capital Disclosure, Cash Holding, and Foreign Ownership on Firm Financial Performance - Avilya Baysta Bheda Wea; Sisilia Rachel Ari Putri (Journal of Accounting and Auditing, 2026)
Purpose – This study aims to obtain empirical evidence on the The Effect of Green Intellectual Capital Disclosure, Cash Holding, and Foreign Ownership on Firm Financial Performance Design/methodology/approach – This study uses quantitative research. It utilizes secondary data. The population is 127 industrial companies listed on the Indonesia Stock Exchange between 2022 and 2024. The sample is 70 industrial companies listed on the Indonesia Stock Exchange between 2022 and 2024. The total number of observations in this study is 210. The analysis technique used to test the hypotheses is multiple regression analysis using Eviews9 software Findings – The results of this study indicate that the Green Intellectual Capital variable has a negative and significant effect on financial performance. The cash holding variable has a negative and significant effect on financial performance. The foreign ownership variable has a positive and significant effect on financial performance. Research limitations/implications – This study aims to provide information regarding the financial performance of companies in the financial sector and can be useful for decision-making as well as serve as a reference for further research.